Temperature and Light Response Index (RI) on Seed Germination of Hippophae Salicifolia D.Don - Tomar, Anita; Rattan, Vidya (Indian Forester, 2013)
Hippophae salicifolia D.Don is a deciduous tree species restricted to the Himalayan region. Seeds of H. salicifolia were collected from Uttarakhand State three provenances. Experiments were conducted in order to investigate different temperatures and lights response index in germination behavior of H. salicifolia seeds. The highest mean germination was obtained at 25°C. Therefore , it is recommended that ±25°C can be considered optimum temperature for its seed germination under controlled conditions. The light study revealed that maximum germination percentagewas found in red light followed by yellow light and minimum germination observed in green light. Provenance of Chamoli was the best as compared to Uttarkashi and Pithoragarh.